2015
DOI: 10.1590/1983-084x/14_031
|View full text |Cite
|
Sign up to set email alerts
|

Teor, rendimento e composição química do óleo essencial de plantas de manjericão submetidas ao estresse salino com NaCl

Abstract: RESUMO:O objetivo do presente trabalho foi avaliar o teor, o rendimento e a composição química do óleo essencial de manjericão (Ocimum basilicum L.) submetido ao estresse salino por NaCl. Para tanto, o experimento foi conduzido em casa de vegetação, sob delineamento inteiramente casualizado, caracterizado por 5 (cinco) tratamentos de NaCl, adicionados à água de irrigação (0,01 -controle,T1; 1,2 -T2; 2,3 -T3; 3,4 -T4 e 4,5 dS m -1 -T5, correspondendo respectivamente a 0,1; 12,0; 23,0; 34,0 e 45,0 mM ), com 4 (q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 12 publications
1
9
0
4
Order By: Relevance
“…Furthermore, another study of various cultivars of basil (including the Genovese Gigante) asserted that, with regards to the main compounds, all the cultivars were characterized by a high relative percentage of linalool (41-76%) and relatively abundant amounts of 1,8-cineole (1-12%), τ-cadinol (2-8%), and trans-α-bergamotene (1-3%) during the flowering stage (Marotti et al, 1996) -which is in accordance with our results. In addition, the relative percentage which the samples presented (except for the WS samples) regarding eugenol (7.1-21.3%) agrees with the relative percentage obtained for this compound in EO samples of O. basilicum L. grown in Portugal (9.7-17.6%) (Roque, 1991). The chemical analysis enabled us to confirm that this cultivar is the Genovese Gigante.…”
Section: Essential Oils Compositionsupporting
confidence: 80%
“…Furthermore, another study of various cultivars of basil (including the Genovese Gigante) asserted that, with regards to the main compounds, all the cultivars were characterized by a high relative percentage of linalool (41-76%) and relatively abundant amounts of 1,8-cineole (1-12%), τ-cadinol (2-8%), and trans-α-bergamotene (1-3%) during the flowering stage (Marotti et al, 1996) -which is in accordance with our results. In addition, the relative percentage which the samples presented (except for the WS samples) regarding eugenol (7.1-21.3%) agrees with the relative percentage obtained for this compound in EO samples of O. basilicum L. grown in Portugal (9.7-17.6%) (Roque, 1991). The chemical analysis enabled us to confirm that this cultivar is the Genovese Gigante.…”
Section: Essential Oils Compositionsupporting
confidence: 80%
“…Bernstein et al (2010) verified an increase in essential oil content using seedlings of basil, cultivar "Perrie", under salt conditions. In contrast, Alves et al (2015) reported a decrease in oil yield in basil (unidentified cultivar), with further increases of salinity. In our work, the results clearly show that, in the 'Gennaro de Menta' cultivar, the essential oil content, yield, and productivity are increased by both salt stress and H 2 O 2 application.…”
Section: T1 T2 T3 T4mentioning
confidence: 86%
“…It is cultivated for the in natura trade and mainly for the industrial production of essential oils widely used in the pharmaceutical industry (Lorenzi and Matos, 2008). According to Alves et al (2015), the highest concentrations of essential oil are found in leaves, floral calyces, secretory channels, and glandular hairs. In addition, the amount of oil may be affected by environmental stresses such as water deficit and salinity, but this effect depends on factors such as type, intensity, and duration of the stress (Alves et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The oil was extracted from the leaves, which were separated from the stems after drying. In a 30 g sample of ground leaf dry biomass (LDB) as previously established by Alves et al (2015), the oil was extracted with hydrodistillation using a Clevenger apparatus (Clevenger, 1928). The distillation time (2 h) was counted from the moment the first drop of essential oil was deposited in the collector.…”
Section: Nutrient Solution and Experiments Managementmentioning
confidence: 99%